TAFSIR PSIKOSPIRITUAL TERHADAP SURAH AL-DUHA DAN TERAPI UNTUK KELESUAN EMOSI: SATU ANALISIS KRITIKAL: A PSYCHOSPIRITUAL EXEGESIS OF SURAH AL-DUHA AND THERAPEUTIC INTERVENTIONS FOR EMOTIONAL FATIGUE: A CRITICAL ANALYSIS - Tahir, Ammar Abdullah; Abdullah, Saufi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Artikel ini menganalisis Surah ad-Duḥā daripada perspektif tafsir psikospiritual dengan menelusuri potensinya sebagai terapi terhadap kelesuan emosi (emotional exhaustion). Dalam konteks cabaran psikologi moden yang dicirikan oleh tekanan jiwa, kemurungan ringan dan kehilangan makna hidup, al-Qur’an dilihat bukan sekadar sumber hukum, tetapi juga wahyu penyembuhan (shifā’) bagi kesejahteraan rohani dan emosi. Melalui pendekatan tafsir tematik (tafsir maudhu‘ī) dan analisis psikospiritual, kajian ini menggabungkan pandangan ulama klasik seperti al-Ṭabarī, al-Qurṭubī dan Ibn Kathīr dengan pemikiran kontemporari Malik Badri dan Abdullah Rothman bagi membina kefahaman menyeluruh tentang struktur terapi dalam Surah ad-Duḥā. Hasil analisis mendapati surah ini mengandungi empat dimensi terapi utama: kognitif (tauhid), emosi (syukur), spiritual (rūḥānī), dan sosial (iḥsān). Ia berfungsi sebagai kerangka pemulihan jiwa yang progresif — bermula dengan penenangan emosi, pemulihan harga diri, refleksi sejarah hidup, dan berakhir dengan dorongan amal kebajikan. Kajian ini turut menegaskan bahawa mesej terapeutik Surah ad-Duḥā sejalan dengan prinsip cognitive reframing (CBT), meaning-making (Logotherapy), dan positive affirmation (Positive Psychology), namun berbeza dari segi epistemologi kerana berasaskan wahyu Ilahi. Secara keseluruhannya, kajian ini menyumbang kepada pengukuhan bidang psikoterapi Islam dengan mencadangkan model terapi Qurani berasaskan empat dimensi Tauhid–Syukur–Ruhani–Ihsan sebagai asas bagi pembinaan modul intervensi psikospiritual kontemporari. This article analyzes Surah ad-Duḥā from a psychospiritual exegesis perspective by exploring its potential as a therapeutic framework for emotional exhaustion. In the context of modern psychological challenges characterized by mental stress, mild depression, and the loss of life’s meaning, the Qur’an is viewed not merely as a source of law, but also as a divine revelation (shifā’) that provides healing for spiritual and emotional well-being. Employing a thematic exegesis (tafsīr mawdhū‘ī) and psychospiritual analytical approach, this study integrates the insights of classical scholars such as al-Ṭabarī, al-Qurṭubī, and Ibn Kathīr with the contemporary perspectives of Malik Badri and Abdullah Rothman to construct a holistic understanding of the therapeutic structure within Surah ad-Duḥā. The analysis reveals that the surah embodies four core therapeutic dimensions: cognitive (tawḥīd), emotional (gratitude), spiritual (rūḥānī), and social (iḥsān). It functions as a progressive model of soul restoration—beginning with emotional reassurance, self-worth recovery, reflective gratitude on personal history, and culminating in the motivation for social benevolence. The study further asserts that the therapeutic message of Surah ad-Duḥā aligns with principles of cognitive reframing (CBT), meaning-making (Logotherapy), and positive affirmation (Positive Psychology), yet differs epistemologically by being founded on divine revelation. Overall, this study contributes to strengthening the field of Islamic psychotherapy by proposing a Qur’anic-based therapeutic model grounded in the four interrelated dimensions of Tawḥīd–Shukr–Rūḥānī–Iḥsān, which serves as a conceptual basis for developing contemporary psychospiritual intervention modules.